Studi Fenomenologi Peran Guru Sekolah Dasar Sebagai Fasilitator dalam Pembelajaran Tematik di Kelas Tinggi - Husni Mubarok; Syailin Nichla Choirin Attalina (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to describe the role of the teacher as a facilitator in thematic learning. In this study, the approach taken by the researcher is to use a qualitative phenomenological approach with triangulation of sources, which includes fifth grade science teachers and fifth grade students at SD Negeri 5 Jambu. Data collection techniques in the form of interview techniques. The results of this study indicate that the role of the teacher in Class V of SD Negeri 5 Jambu has carried out its role as a facilitator according to the indicators except for the aspect of delivering material via video conference. The factors that hinder teachers from carrying out their role as facilitators are 1) Lack of student interaction in learning, 2) Limited learning time, 3) Teacher workload in administration, 4) Lack of parental support in learning.